2006
DOI: 10.1007/s00270-005-0138-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebroplasty for Osteoporotic Compression Fracture: Multivariate Study of Predictors of New Vertebral Body Fracture

Abstract: We identified 59 new fractures in 30 of the 83 patients: 41 new fractures in vertebrae adjacent to treated vertebrae; and 18 new fractures in vertebrae not adjacent to treated vertebrae. New fractures occurred in vertebrae adjacent to treated vertebrae significantly more frequently than in vertebrae not adjacent to treated vertebrae. Only cement leakage into the disk was a significant predictor of new vertebral body fracture after vertebroplasty (odds ratio = 4.633). None of the following covariates were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
105
6
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 11 publications
9
105
6
2
Order By: Relevance
“…No complications of extravasation into the veins, soft tissue, or disk were observed. Other investigators have found a relationship between extravasation of cement into the disk and the occurrence of new VCFs 18,26 ; however, our study did not identify extravasation of cement into the disk (which occurred in 17% of the treated vertebrae) as a significant predictor of subsequent secondary adjacent VCFs.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…No complications of extravasation into the veins, soft tissue, or disk were observed. Other investigators have found a relationship between extravasation of cement into the disk and the occurrence of new VCFs 18,26 ; however, our study did not identify extravasation of cement into the disk (which occurred in 17% of the treated vertebrae) as a significant predictor of subsequent secondary adjacent VCFs.…”
Section: Discussioncontrasting
confidence: 55%
“…13,14 However, in our study, the volume of cement injected was not found to be a significant predictor of subsequent secondary adjacent VCFs, a finding that is in agreement with those of others. 17,18 The results of a recent biochemical study, 19 which investigated the effects of bone mineral attenuation on the mechanical strength and stiffness of vertebral bodies left untreated (intact) or 4%, 12%, or 24% filled with cement, showed that only the highest fill volume resulted in improved stiffness relative to the untreated fractures. However, the stiffness was not restored to prefracture levels, and improvements in stiffness and strength were found to depend significantly on bone attenuation, with highly osteoporotic vertebrae showing the least benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Cement leakage into the disk space is controversial because some studies have shown an increased risk for subsequent fractures of adjacent vertebral bodies, 33,34 whereas others have claimed that cement leakage into the disk space is of no clinical significance. 10,35 It is hypothesized that the use of expandable balloons in kyphoplasty would result in better height restoration than in vertebroplasty in which the cement is injected directly into the fractured and collapsed vertebral body.…”
mentioning
confidence: 99%
“…Various reasons and risk factors for fractures that occur following VP have been discussed: increased stiffness in the vertebra treated [34,42], cement formation of a solid mass rather than interdigitation [43], changes in load transfer [44,45], an altered loading direction [46], cement leakage into the disc (pro: [12,14,21,[47][48][49], contra: [50]), use of too much cement [15,49], the degree of vertebral height restoration [12,15] and persistent local kyphosis [20], deflection of the endplate and the intervertebral disc into adjacent vertebra [34], fracture shape [51], pre-existing fracture [12,23], advanced patient age [23], ongoing osteoporosis [16,20,24], and low BMD [12,16,19,21,23], and a high number of VPs at baseline [16,26]. In addition, patients with high parathyroid hormone concentrations, low body mass index, no use of back brace, no anti-osteoporosis therapy, history of metabolic disease, and use of drugs which influence bone metabolism tend to have a greater risk of recurrent fractures [16,17,47].…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications, possibly due to the addition of a material that is stiffer than the surrounding bone, include fractures of the augmented and adjacent vertebrae. New osteoporotic vertebral compression fractures, in the months after VP, are reported in 7-63 % of VP patients, up to 82 % of these occur at the adjacent levels, with adjacent fractures occurring sooner than nonadjacent fractures; rates of recurrent fracture of the augmented vertebra itself range up to 63 % in the literature [1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. It is still under debate whether new vertebral fractures appear more often in patients who received cement augmentation than in conservatively treated patients; some studies support this hypothesis [1,6,7,[27][28][29], while others question it [2,3,26,30].…”
Section: Introductionmentioning
confidence: 99%